Implementation and evolution of mitigation measures, testing, and contact tracing in the National Football League, August 9-November 21, 2020 - Mack, C. D.; Wasserman, E. B.; Perrine, C. G.; MacNeil, A.; Anderson, D. J.; Myers, E.; Smith, S.; McDonald, L. C.; Osterholm, M.; Solomon, G. S.; Mayer, T.; Sills, A. (Morbidity and Mortality Weekly Report (MMWR), 2021)
Summary What is already known about this topic? COVID-19 contact tracing is important to prevent transmission, but risk characterization is difficult. What is added by this report? The National Football League observed SARS-CoV-2 transmission after <15 minutes of cumulative interaction, leading to a revised definition of a high-risk contact that evaluated mask use and ventilation in addition to duration and proximity of interaction. Intensive mitigation protocols effectively reduced close interactions. What are the implications for public health practice? Assessment of the context of each interaction, including mask use, indoor versus outdoor setting, and ventilation, in addition to duration and proximity, can improve identification of high-risk contacts during contact tracing. Postexposure quarantine based on redefined high-risk criteria, combined with testing and environment-specific intensive protocols, can protect communities before and after case identification.